CROP DISEASES AND PESTS AND THEIR CONTROL MEASURES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article provides information about the importance of cereals in the national economy, beneficial properties, as well as biology, development and harm of harmful organisms.